Assessing the Detonation Performance of New Tetrazole Base High Energy Density materials. Issue 12 (27th September 2018) - Jafari, Mohammad; Ghani, Kamal; Keshavarz, Mohammad Hossein; Derikvandy, Fatemeh
Abstract: Tetrazole derivatives containing energetic groups can be considered as high energy density materials due to their high positive standard enthalpies of formation and high densities. The effects of two energetic groups −NO2 and −N3 as well as stabilizing group −NH2 and methyl group are investigated for assessment of detonation performance of 50 tetrazole derivatives where 12 derivatives have been synthesized. The velocities of detonation and detonation pressures are estimated on the basis of two new predictive methods, which require the condensed phase standard enthalpy of formation (Δ f H°c ) and crystal density ( ρ ). Quantum mechanical and quantitative structure‐property relationship (QSPR) methods are used for calculation of Δ f H°c . In order to calculate the ρ values, the electrostatic potentials mapped onto the 0.001 a.u. isosurface of electron densities of isolated molecules is used. Detonation performances of tetrazole derivatives are compared to three common high explosives, i. e. TNT, RDX, and HMX. Among many tetrazole derivatives, four new tetrazole derivatives are introduced as new potential high energy density materials. Abstract :